Calcareous plankton events at the Early/Middle Miocene transition of DSDP Hole 608: comparison with Mediterranean successions for definition of the Langhian GSSP - Di Stefano, A.; Verducci, M.; Cascella, A.; Iaccarino, S. M. (Micro Press, 2011)
We propose a revision of the calcareous plankton biostratigraphy of the upper Burdigalian/early Langhian interval (Early/MiddleMiocene) of theDSDPHole 608 succession (northeastern Atlantic Ocean), one of themost complete open-ocean Miocene sequence. We detected a set of calcareous plankton events through a 26m thick succession (320-346 mbsf), spanning the interval from 14.969 to 17.268 Ma, chronologically constrained through paleomagnetic and astrochronological data. “Standard” bioevents were tested and in some cases they resulted poorly applicable to the investigated succession. Conversely, the quantitative biostratigraphic analysis highlighted additional biohorizons (Helicosphaera ampliaperta Last CommonOccurrence, Sphenolithus heteromorphus Paracme Interval, Paragloborotalia siakensisAcme “a”) considered till now restricted to theMediterranean region. This results in a better applicability of Mediterranean zonal schemes, providing a higher biostratigraphic resolution. Our results point out strict affinity between Atlantic and Mediterranean successions in Early/MiddleMiocene. Thus, in the perspective of establishing the Langhian GSSP, that according to the historical criterion must be located in the Mediterranean region, our results provide significant correlation tools between Mediterranean and open-ocean successions. Published xxx-xxx 2.2. Laboratorio di paleomagnetismo JCR Journal reserved